Trajectory planning method of mobile piezorobot - Bansevičius, Ramutis; Drukteinienė, Asta; Kulvietis, Genadijus (Lietuvos matematikos rinkinys, 2009)
This paper presents analysis of trajectory planningmethods for mobile robots and new trajectory planning method research for mobile piezorobots. Here are deduced motional simultaneous equations for this kind of robots that describe point-to-pointmotion by given function. Preliminary experimental results prove the feasibility of proposed mathematical model.
Keywords: mobile piezorobot; piezoelectric actuator; trajectory planning method